STRUCTURE, FUNCTION AND VALUE THE TRADITION OF ORAL LITERATURE IN SUMENEP MADURA - M. Ridwan; Agus Wahdian (ISLLAC : Journal of Intensive Studies on Language, Literature, Art, and Culture, 2017)
The purpose of this research is: first, describe the structure, function and value of oral literature in Sumenep Regency. Second, obtain data objectively about the oral literary tradition in Sumenep Regency. Third, it examines the structure, function and value of oral literary tradition as one of theentertainment media, adhesives and silaturrahim forming mental as well as compiling Textbook-based Indonesian Language Education Oral literary tradition with ISBN. Indonesia as the country with the symbol of Bhinneka Tunggal Ika must uphold all forms of diversity and ethics that is rahmatan lil ' alamin. Indonesia is made up of many different tribes, ethnicities, cultures, religions, languages and traditions must maintain the integrity of the Union and the unity of the nation. It is this diversity that later gave birth to traditional knowledge andcultural expressions that are not owned by other Nations in the world. Oral literary tradition that developed in the island as a manifestation of the real cultural archipelago that is a spirit that needs to be preserved by generations and community supporters. This research is one of the endeavor to take good care of the legacy of tradition and culture which flourished in the archipelago.